Acute myeloid leukemia with NPM1, IDH1 and IDH2 mutations in Paraguayan patients - Franco-Benegas, Lady; Mujica, Maria Paz; Jolly, Valerie; Salinas, Victor; Zarza, Jose; Gonzalez, Diana; Di Tore, Denisse; Morel, Laura; Bogado, Juan Jose; Labrano, Monica; Leiva, Samadi; Ovando, José Manuel; et al. (Medicina Clínica y Social, 2025)
Introduction: Acute myeloid leukemia (AML) arises from the clonal expansion of myeloid blasts in peripheral blood, bone marrow, or other tissues. Its etiology is associated with the development of genetic mutations. Identifying actionable mutations is clinically relevant for the diagnosis, prognosis, and treatment of AML. Objective: To identify and describe the mutation profile of the NPM1, IDH1, and IDH2 genes in Paraguayan patients diagnosed with AML. Methodology: A retrospective molecular epidemiological study was conducted on 32 AML patient samples harboring NPM1 mutations. Real-time PCR and Sanger sequencing were performed to detect genetic variants. Results: The most frequently detected NPM1 mutation was type A, identified in 94% (30/32) of cases. Additionally, IDH1 and IDH2 mutations were found in 40% (13/32) of cases, with the IDH2 R140Q variant being the most predominant. The most frequent co-occurrence of mutations was observed between NPM1 and IDH2. Conclusion: This study provides valuable insights into the mutational profile of NPM1, IDH1, and IDH2 in AML patients in Paraguay, highlighting the relevance of these markers for risk stratification and their potential benefit for targeted therapies.
Keywords: Acute Myeloid leukemia; NPM1; IDH1; IDH2; molecular diagnosis